2013
DOI: 10.4236/ojoph.2013.34024
|View full text |Cite
|
Sign up to set email alerts
|

Cryotherapy in Ophthalmology

Abstract: Cryogens have been used to freeze living tissue for the purpose of treating benign and malignant lesions. Within the last century, ophthalmologists have found cryotherapy to be useful in treating a variety of ocular pathologies. Here, we review the history of cryotherapy, its introduction to the field of ophthalmology, its proposed mechanism of action, and its current applications in treating surface and intraocular eye disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 98 publications
(105 reference statements)
0
7
0
Order By: Relevance
“…Cryotherapy of the tumor bed and margins is also an upcoming recommendation at many centers. 12 Updated cryosurgery provides a low cost option to MMS. 13 Cryosurgery preserves much healthy ocular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Cryotherapy of the tumor bed and margins is also an upcoming recommendation at many centers. 12 Updated cryosurgery provides a low cost option to MMS. 13 Cryosurgery preserves much healthy ocular structures.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, H&E stained sections of cryo‐injured mice demonstrated retinal injury. Tissue cracking could be explained by the removal of the probe after its adherence to the tissue before being defrosted, over freezing by excessive cold temperatures or prolonged duration with production of toxic concentrations of solutes inside cells, increased intra‐ocular pressure by freezing the intraocular fluid which expands in volume, denaturation of lipid–protein complexes, osmotic stress, and the intra‐ and extracellular ice crystals causing necrosis and apoptosis .…”
Section: Discussionmentioning
confidence: 99%
“…Different ophthalmic conditions, including surface and intraocular pathology, could be treated by cryotherapy which is also known as cryocautery or cryosurgery. In spite of its useful uses, the freeze phase of cryotherapy can cause cellular destruction with multifactorial mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…During removal, the base is cauterized. Cryotherapy is also applied to all the conjunctival margins [127].
Fig.
…”
Section: Main Textmentioning
confidence: 99%